Optimal Bi₀.₈Ba₀.₂FeO₃ doping in Bi₀.₅(Na₀.₇₇K₀.₂₀Li₀.₀₃)₀.₅TiO₃ multiferroic ceramics synthesized by the solid-state combustion technique - Pichittra Thawong; Sasipohn Prasertpalichat; Tawat Suriwong; Supree Pinitsoontorn; Pongsakorn Jantaratana; Suphornphun Chootin; Manlika Sriondee; Thitirat Charoonsuk; Naratip Vittayakorn; Aurawan Rittidech; Theerachai Bongkarn (Scientific Reports)
Abstract (1-x)Bi0.5(Na0.77K0.20Li0.03)0.5TiO3-xBi0.8Ba0.2FeO3 ((1-x)BNKLT-xBBF) ceramics with x = 0-0.4 were synthesized by the solid-state combustion technique. X-ray diffraction (XRD) analysis confirmed a pure perovskite structure with coexisting rhombohedral and tetragonal phases. Rietveld refinement revealed that the unit cell volume increased with increased x due to the substitution of smaller Bi3+ and Ti4+ ions by larger Ba2+ and Fe3+ ions at the A- and B-sites, respectively. The average grain size and measured density also increased with increasing x, while the resistivity decreased. At room temperature, (1-x)BNKLT-xBBF ceramics with x = 0.2–0.4 exhibited multiferroic behavior, characterized by ferroelectric and ferromagnetic hysteresis loops. The 0.8BNKLT-0.2BBF ceramic exhibited the most favorable properties, including: the highest relative density (95.48%), the highest dielectric constant and low dielectric loss at room temperature (εR = 1746 and tan δR = 0.0296), good ferroelectric properties (Pr=6.46 µC/cm2 and Ec=11.84 kV/cm) and good ferromagnetic properties (Mr=0.002 emu/g, Hc=110 Oe and αE = 1.092 mV/Oe·cm). These results indicate that 0.8BNKLT-0.2BBF has the potential for applications in lead-free, room temperature multiferroic applications.